A Degradation Kinetic Study on Pyrolysis of Three Biomass Samples and Co-pyrolysis of Hazelnut Shell and Ultra-high Molecular Weight Polyethylene Blends Using a Silver Indicator - Aydinli, B.; Caglar, A. (Informa UK Limited, 2013)
A kinetic study was proposed in pyrolysis process supplementary to thermo-gravimetric analysis. Three different biomasses, hazelnut shell, olive residue, and tea waste, and hazelnut shell and ultra-high molecular weight polyethylene mixture were analyzed kinetically in a batch-type tubular pyrolysis reactor. Reaction times were measured with the changing color of silver indicator, which was attached to the terminal of pyrolysis set up at various specified temperatures between 623 and 923 K. The Arrhenius plots were obtained and the activation energies (Ea ) of reaction values were calculated from the slope of linear curves. For pure biomass, two linear degradation zones were detected possibly belonging to cellulose and hemicellulose. In the case of hazelnut shell and ultra-high molecular weight polyethylene mixtures, linearity of Arrhenius plots were grasped with the modification of the pre-exponential factor of the basic Arrhenius equation. This type of kinetic method directly involves the basic paramete...
Keywords: 7. Clean energy